Legal Practices of Employment Agreements, Power Relations, and Identity Politics of Indonesian Women Domestic Workers - Rismawati, Shinta Dewi; Rahmawati, Rita; Devy, Happy Sista; Septiadi, Muhammad Andi; Thoha, Silvia Milady Azkiya (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2023)
This research aims to analyze the legal practice of the employment agreement of women domestic workers when they enter into a work contract with their employers in Surakarta City, then to identify patterns of power relations between women domestic workers and their employers when they make their work agreements, and finally to explain the identity politics that attached to women domestic workers when they work in their employer's family. To analyze this phenomenon, a socio-legal study with a qualitative research approach is used. The results of the study show that the practice of working agreements between women domestic workers and their employers even though the work agreements are made in unwriiten, but in fact the values are in accordance with the essence of contract law as regulated in the provisions of the Civil Code (KUHPerdata). The work agreement shows a contractual and contextual dimension. The working relationship between them is based on a sense of interdependence and high trust between one another. This pattern of giving and receiving can ultimately able to reflect the existence of an equal power relationship between the two when making a work agreement. Even though women domestic workers have been labeled as helpless, they have a confident character and are autonomous in completing their work agreements. This equal relationship can make the relationship between the two very close and intense. This condition has implications for the political transformation of the identity of women domestic workers from outsiders who become part of the insider of the temporary employer's family